2018
DOI: 10.1038/s41467-018-07075-3
|View full text |Cite|
|
Sign up to set email alerts
|

Photoreduction of gaseous oxidized mercury changes global atmospheric mercury speciation, transport and deposition

Abstract: Anthropogenic mercury (Hg(0)) emissions oxidize to gaseous Hg(II) compounds, before deposition to Earth surface ecosystems. Atmospheric reduction of Hg(II) competes with deposition, thereby modifying the magnitude and pattern of Hg deposition. Global Hg models have postulated that Hg(II) reduction in the atmosphere occurs through aqueous-phase photoreduction that may take place in clouds. Here we report that experimental rainfall Hg(II) photoreduction rates are much slower than modelled rates. We compute absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
192
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 136 publications
(201 citation statements)
references
References 71 publications
7
192
0
2
Order By: Relevance
“…The Hg that is emitted from anthropogenic (and natural) sources to air is almost exclusively inorganic as elemental (Hg 0 ) and divalent compounds (Hg II ) in gaseous and particulate forms (Obrist et al, 2018). Redox reactions between Hg 0 and Hg II in the atmosphere are primarily photochemically driven (Ariya et al, 2015;Saiz-Lopez et al, 2018), with the bulk of the atmospheric Hg deposited onto the Earth's surface (oceans, land, and freshwaters) being in the form of inorganic Hg II . The aquatic environment also receives Hg input, primarily as inorganic Hg II , from rivers,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hg that is emitted from anthropogenic (and natural) sources to air is almost exclusively inorganic as elemental (Hg 0 ) and divalent compounds (Hg II ) in gaseous and particulate forms (Obrist et al, 2018). Redox reactions between Hg 0 and Hg II in the atmosphere are primarily photochemically driven (Ariya et al, 2015;Saiz-Lopez et al, 2018), with the bulk of the atmospheric Hg deposited onto the Earth's surface (oceans, land, and freshwaters) being in the form of inorganic Hg II . The aquatic environment also receives Hg input, primarily as inorganic Hg II , from rivers,…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relationship between anthropogenic Hg emissions to the atmosphere and Hg trends in aquatic biota is influenced by many environmental and ecological factors (e.g., temperature, light intensity, pH, redox condition, organic carbon and nutrient concentrations, and food web structure and dynamics) that control the rates of Hg deposition from the atmosphere, MeHg production (methylation) and degradation (demethylation) in the aquatic environment, and the uptake of Hg, especially MeHg, by biota Hsu-Kim et al, 2018). The complexity of these processes, along with the large inventories of legacy anthropogenic and natural Hg stored long-term in terrestrial and aquatic systems, suggests that biotic Hg may be only tenuously connected to atmospheric Hg which has a much shorter life-time (0.5 to 2 years) than the decadal or century-scale life-times of Hg in soils and oceans (Horowitz et al, 2017;Saiz-Lopez et al, 2018). Furthermore, even if atmospheric and biotic Hg do follow similar trends, there could be a significant time lag between their response.…”
Section: Introductionmentioning
confidence: 99%
“…The Hg 0 flux measured at the CH-Cha site is comparable to Hg 0 fluxes reported for other grassland sites worldwide . A median Hg 0 flux of 0.4 ng m −2 h −1 and a flux range between −18.7 and 41.5 ng m −2 h −1 (site-based average fluxes) was reported for nine studies (Poissant and Casimir, 1998;Schroeder et al, 2005;Ericksen et al, 2006;Obrist et al, 2006;Fu et al, 2008a, b;Fritsche et al 2008a, b;Converse et al, 2010). Several studies reported net Hg 0 emission during summer.…”
Section: Net Ecosystem Exchange Of Hg 0 Over Grasslandmentioning
confidence: 97%
“…The spring period selected for the 2016 experiment had two main characteristics: a welldefined night and day cycle without a long sunset, avoiding possible incoming solar radiation by diffraction processes over the horizon. There was also the possibility observing atmospheric mercury depletion events (AMDEs) connected with bromine explosion events (Lu et al, 2001;Moore et al, 2014;Schroeder and Munthe, 1998). Unfortunately, these events were not observed as the northern coast of Svalbard was virtually ice free by the time we started sampling.…”
Section: Sampling Period and Strategymentioning
confidence: 99%
“…Mercury is a heavy metal with a known toxicity present in the environment in several different chem-ical forms. It is reactive in the environment and undergoes photochemical reactions that change its speciation and chemical behaviour (Dommergue et al, 2010;Durnford and Dastoor, 2011;Saiz-Lopez et al, 2018;Steffen et al, 2002). Mercury in its oxidized form can be deposited onto the snowpack, increasing Hg concentrations in the upper snow strata (Obrist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%